KOMPOSISI PORTRAIT LANDSCAPE DENGAN OBJEK PEMANDANGAN PADA 12 LOKASI DI BALI - Onkky Wahyu Al Pratama; R. Sulistiyo Wibowo (Politeknik Negeri Media Kreatif, 2014)
Landscape portrait concept is not new, but in its application and use, including rare. In landscape photography, many photographers featuring views of the widest-shaped or landscape (horizontal) and rarely use the portrait (vertical). The research questions are how photographing landscape portrait composition, whether landscape portrait composition can enrich the composition of the landscape, and how the outcome of portrait landscape that can be enjoyed in general. The methods used are observation, exploration on the method of creation, experiment or improvisation, embodiment, and presentation of work. The sceneries in Bali have been selected to provide the different compositions using landscape portrait composition. In photographing the landscape portrait, photographers should use good composition, as in the portrait landscape use good composition can provide the depth dimension of the photograph, so the photos taken can still be attractive at first sight.